1999
DOI: 10.1107/s0108767398007181
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intermolecular interactions on multipole-refined electron densities

Abstract: This work examines the effect of intermolecular interactions on molecular properties derived from simulated X-ray diffraction data. Model X-ray data are computed from a superposition of ab initio molecular electron densities in the crystal, as well as from periodic crystal Hartree-Fock electron densities, for the hydrogen-bonded systems ice VIII, formamide and urea, as well as the weakly bound acetylene. The effects of intermolecular interactions on the electron density are illustrated at both infinite and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 40 publications
6
41
0
Order By: Relevance
“…Figure 4 reports total and interaction ED maps obtained from HF CRYSTAL calculations with a very good (TZPP) GTO set. The picture is very similar to that provided by Spackman et al [69]: with respect to the superposition of molecular densities the most notable feature is a build-up of charge in front of the terminal oxygen, due to the population of the hydrogen bonds with the neighboring molecule and to the corresponding de-population of the N-H intramolecular bonds. [10], but allows both inter-and intra-molecular changes of the ED to be recorded.…”
Section: Environmental Effects On the Dfs Of A Molecular Crystal: Ureasupporting
confidence: 68%
See 1 more Smart Citation
“…Figure 4 reports total and interaction ED maps obtained from HF CRYSTAL calculations with a very good (TZPP) GTO set. The picture is very similar to that provided by Spackman et al [69]: with respect to the superposition of molecular densities the most notable feature is a build-up of charge in front of the terminal oxygen, due to the population of the hydrogen bonds with the neighboring molecule and to the corresponding de-population of the N-H intramolecular bonds. [10], but allows both inter-and intra-molecular changes of the ED to be recorded.…”
Section: Environmental Effects On the Dfs Of A Molecular Crystal: Ureasupporting
confidence: 68%
“…Gatti has recently reviewed the power of this theory using precisely urea as a test case [10] and extending the analysis performed in a pioneering ab-initio HF study [68]: in particular, he demonstrated the ability of topological analysis to describe quantitatively environmental effects on the ED, both as concerns the intermolecular and, indirectly, the intramolecular region (for instance, the appreciable change of the dipole moment of the molecule in the crystal with respect to its gas-phase value). The important discussion about the detectability of environmental effects from diffraction data by Spackman et al [69] is also worth mentioning.…”
Section: Environmental Effects On the Dfs Of A Molecular Crystal: Ureamentioning
confidence: 99%
“…3 closely resembles that of the interaction density for urea ͑the difference between crystal Hartree-Fock calculation and superposition of isolated molecules͒ in Fig. 2 of Spackman et al 63 ͑see also Fig. 7 of Docherty et al 64 ͒, and hence many of the observed effects of wave function fitting for urea can be attributed to hydrogen bonding.…”
Section: B Ureamentioning
confidence: 78%
“…The temperature factors of hydrogen atoms were anisotropically modelled based upon discussions by Hoser et al, 29 Spackman et al [38][39][40] and Koritsansky et al 41 These studies have observed dissimilarities in the topological analysis of weak interactions such as H-bonds , van der Waals forces and π-π stacking interactions. 30 To observe the effect of applying calculated anisotropic temperature factors for hydrogen atoms during multipole refinement, anisotropic temperature factors were calculated 31 9 Our findings show that the use of anisotropic temperature factors…”
Section: Isotropic Vs Anisotropic Refinement Of Hydrogen Atomsmentioning
confidence: 99%